Alignment and Success: Applying the Hierarchy of Planning and the Needs‐Assesment Hierarchy. Issue 7 (28th August 2019) - Kaufman, Roger
Abstract: Performance Improvement is conventionally focused on the workplace and on work. That is successful some of the time. However, the symptom of a problem may be at the work level, while the problem or opportunity is somewhere else, such as with a faulty product or service, poor supervision, offering a deliverable that isn't what the customer really requires, or not starting planning at the external client's or the societal level. Knowing and using the hierarchy of planning and the needs assessment hierarchy (Kaufman, 2018) may help to ensure that what you do and deliver is worthy. This article is about how to avoid quick fixes by dealing, not with the symptoms, but with the root causes.